PENGARUH HARGA DAN PROMOSI TERHADAP MINAT BELI PRODUK HUNGTATA - Tanata, Hungga Fernando; Chirstian, Sonata (Jurnal Performa: Jurnal Manajemen dan Start-up Bisnis, 2021)
The purpose of this research is to determine the influence of price and promotion on the purchase intention of Hungtata. Hungtata is a company that sells healthy drink products made from fresh and natural juice. This research is based on the surveys conducted towards potential customers of Hungtata regarding price, promotion, and purchase intention. The population of this study were 320 people who knew and followed Hungtata's social media account. Sampling using purposive sampling method with a total of 65 respondents who knew and had never bought Hungtata products. This research uses SPSS software to perform quantitative analysis on the research data. Research results indicate that price and promotion significantly influence the purchase intention of Hungtata.  Keywords: Price, Promotion, Purchase intention.